“Subarachnoid block in active burn injury”: A case report of anesthetic challenges and considerations - Rutuja Gohad; Sudha S. Jain; Shubham Rahane; Dushyant Bawiskar (Journal of Family Medicine and Primary Care)
Anesthetists pose different challenges in burn cases associated with polytrauma. Here, we present a case of a 35-year-old male electrician with an electric burn and a fall from height who sustained major chest trauma (hemothorax, pneumothorax, emphysema, and multiple rib fracture, and bilateral femur fracture). The collocated burn over the spinal region posed the challenge to administering a subarachnoid block, which was overcome with a paramedian approach anesthesia. The surgical outcome was good, and the patient was stable post-surgery. The paramedian approach provides an excellent alternative to the midline approach for spinal anesthesia. It should be considered in burn patients where it is impossible for the patient to flex, where the intervertebral space is very low, or when there is a burn present over the spinal region. Ultimately, early therapy and mobility goals, two essential components of burn care and rehabilitation, can be achieved with the use of paramedian regional anesthesia.